UHF [videorecording (DVD)] - Yankovic, Al, 1959-; McCarthy, Kevin, 1914-2010; Jackson, Victoria, 1959-; Richards, Michael, 1949-; Bowe, David, 1964- (Metro-Goldwyn-Mayer Studios, 2015)
George Newman is a daydreamer whose hyperactive imagination keeps him from holding a steady job, that is, until he becomes the general manager of Channel 62, a local television station that his uncle wins in a poker game.